2011
DOI: 10.5507/ag.2011.015
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the beginning of the early flight phase of the ski jump in athletes with different performance levels

Abstract: BACKGROUND:Obtaining a long jumping distance is necessary in order to succeed among the best competitors in the Nordic combined. The body movement during the take off and early fl ight is considered to be the most important factor for length of the jump.OBJECTIVE: The purpose of this study was to assess the technique of the start of the early fl ight phase among three groups of Nordic combined competitors representing diff erent performance levels, and to compare them with a group of ski jumpers.METHODS: Thirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
5
1
Order By: Relevance
“…The comparative analysis of sky jumpers technical fitness which is carried out by us is made according to number of scientific works [1,3,7,12,14], in which kinematic indicators of athletes jump technique in different phases are similarly investigated. At the same time information technologies are important component of preparation in ski jumping for a long time by means of which scientists have opportunity to investigate recent trends in jump technique [5,6].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparative analysis of sky jumpers technical fitness which is carried out by us is made according to number of scientific works [1,3,7,12,14], in which kinematic indicators of athletes jump technique in different phases are similarly investigated. At the same time information technologies are important component of preparation in ski jumping for a long time by means of which scientists have opportunity to investigate recent trends in jump technique [5,6].…”
Section: Resultsmentioning
confidence: 99%
“…Study and generalization of the scientific-methodical literature; pedagogic observation; video filming with the video analysis on the basis of the software Dartfish (version 4.0). They were carried out according to the recommendations stated in a number of scientific works [3,4,7,12,13,14]. For creation of information database the software Microsoft Access 2016 was used.…”
Section: Methodsmentioning
confidence: 99%
“…11 Yet, the athletes have to transfer their CoM anterior, 8 in order to enter the flight phase in an optimal aerodynamic position. 3 This results in reduced drag and increased lift forces. 10 This transfer of the COM is further decisive to control the rotational component of the resulting ground reaction force and therefore determines changes in athlete's angular momentum during the take-off.…”
Section: Discussionmentioning
confidence: 99%
“…1 This is why the take-off has received a lot of attention in biomechanical studies. It was for example shown that elite ski jumpers demonstrate a significant higher knee extension velocity during the take-off compared to athletes of a lower performance level 2 as well as compared to nordic combined athletes 3…”
Section: Introductionmentioning
confidence: 99%
“…Reliability based on repeat digitization of a sample sequence was < 1% for temporal and spatial parameters and < 4.5% for velocity parameters. The data were manually digitized by an experienced researcher (Janura, Cabell, Svoboda, Elfmark, & Janurová, 2011;Janura, Cabell, Svoboda, Elfmark, & Zahálka, 2011).…”
Section: Discussionmentioning
confidence: 99%